Optical transitions and nonreciprocity in spatio-temporally periodic layers of spherical particles - E. Panagiotidis; E. Almpanis; N. Papanikolaou; N. Stefanou (Advanced Optical Materials, 2023)
An extension of the photonic layer multiple scattering methodology to dynamic spherical scatterers, which exhibit a periodic time-varying response, is presented. The applicability of the method is demonstrated on specific examples of single- and bi-layers of periodically modulated high-refractive-index spherical particles arranged on a square lattice. The results provide compelling evidence for strong and tunable inelastic scattering effects under the triple resonance condition, fulfilled for optical transitions between neighboring high-Q lattice modes of the appropriate symmetry, which originate from multipolar Mie resonances. A consistent interpretation of the underlying mechanisms is provided and potential applications in the design of nonreciprocal devices are discussed.